Empowering women's entrepreneurship: The role of green knowledge, innovation, and family support - Yanying Zhang; Hui Wang; Kengcheng Zheng; Wanjun Yang (Journal of Innovation & Knowledge (JIK), 2025)
In the current era, women are often recognized as successful entrepreneurs due to their innovative capabilities and strong drive for robust economic growth. Their effective role in job creation, family income etc. is now recognized at an international level. Given the significant contribution, this study explores the factors influencing women's entrepreneurial success. The study underlines the effective role of family support in strengthening the relationship between green knowledge, innovation capabilities, and green social behaviour and women's entrepreneurial success. The data for the study was collected from women entrepreneurs in China using survey questionnaire, adopted from previous studies. The researchers analysed the data using SmartPLS by applying partial least squares structural equation modelling. Findings indicate that green knowledge, green social behavior and innovative capabilities positively influence women's entrepreneurial success. The moderation results show that family support significantly moderates the relationship between green knowledge and women's entrepreneurial success. However, family support appears to be an insignificant moderator in the context of green social behaviour. Our results explain that the significance of family support varies among women, based on their family dynamics. In some cases, family support plays essential role, while in other scenarios, the relevance diminishes when alternative support systems including strong network and adaptability, prove more beneficial. In certain culture, family support is indeed a significant element but primarily within personal domains only. Thus, it can be concluded that in some contexts women's entrepreneurial success is viewed as an independent factor, separated from family dynamics, especially where individual's achievements, regardless of gender, are admired and celebrated.
Keywords: O36; G10; 650; Green knowledge; Innovation capabilities; Green social behaviour; Women's entrepreneurial success; Family support